Innovative Ruangguru’s Educational Product Strategy to Meet Generation Z’s Needs: Insights from Youtube Comments and User Perspectives - Saugi, Wildan; Nurlaili, Nurlaili; Mulawarman, Widyatmike Gede; Yahya, Masrur (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Abstract This study aims to examine how the Clash of Champions (COC) educational product strategy by Ruangguru is responded to by Generation Z through analysis of YouTube comments and user interviews. The main focus of this research is to understand the forms of acceptance, social meaning, and the value of representation and participation that arise in digital interactions with learning innovations. The method used was a qualitative approach with netnography techniques to the top 300 comments on the Ruangguru YouTube channel, as well as in-depth interviews with four students from two universities in East Kalimantan. The results of the study show that COC is not only perceived as a digital learning program, but also as a social space that strengthens motivation, pride, collective identity, and criticism of popular culture that is less educational. Data visualizations such as word cloud, tree maps, and concept maps show that user participation goes beyond passive consumption, by displaying emotional engagement and strong representation drives. These findings underscore the importance of social, affective, and value dimensions in the success of digital educational programs. This research contributes to the development of user-based educational innovations, as well as offers a participatory approach in designing educational strategies that are more inclusive and relevant to the characteristics of the younger generation.